European interlaboratory comparison investigations (ICI) and external quality assurance schemes (EQUAS) for the analysis of bisphenol A, S and F in human urine: Results from the HBM4EU project - Vaccher, Vincent; Lopez, Marta Esteban; Castaño, Argelia; Mol, Hans; Haji-Abbas-Zarrabi, Karin; Bury, Daniel; Koch, Holger M.; Dvorakova, Darina; Hajslova, Jana; Nübler, Stefanie; Kaur Sakhi, Amrit; Thomsen, Cathrine; et al. (Environmental Research, 2022)
The Human Biomonitoring for Europe initiative (HBM4EU) aims to study the exposure of citizens to chemicals and potentially associated health effects. One objective of this project has been to build a network of laboratories able to answer to the requirements of European human biomonitoring studies. Within the HBM4EU quality assurance and quality control scheme (QA/QC), a number of interlaboratory comparison investigations (ICIs) and external quality assurance schemes (EQUASs) were organized to ensure data consistency, comparability and reliability. Bisphenols are among the prioritized substance groups in HBM4EU, including bisphenol A (BPA), bisphenol S (BPS) and bisphenol F (BPF) in human urine. In four rounds of ICI/EQUAS, two target concentration levels were considered, related to around P25 and P95 of the typical exposure distribution observed in the European general population. Special attention was paid to the conjugated phase II metabolites known to be most dominant in samples of environmentally exposed individuals, through the analysis of both native samples and samples fortified with glucuronide forms. For the low level, the average percentage of satisfactory results across the four rounds was 83% for BPA, 71% for BPS and 62% for BPF. For the high level, the percentages of satisfactory results increased to 93% for BPA, 89% for BPS and 86% for BPF. 24 out of 32 participating laboratories (75%) were approved for the analyses of BPA in the HBM4EU project according to the defined criterion of Z-scores for both low and high concentration levels in at least two ICI/EQUAS rounds. For BPS and BPF, the number of qualified laboratories was 18 out of 27 (67%) and 13 out of 28 (46%), respectively. These results demonstrate a strong analytical capability for BPA and BPS in Europe, while improvements may be needed for BPF.
CRIS-Team Scopus Importer:2022-02-25
Keywords: Bisphenols; External quality assurance scheme (EQUAS); HBM4EU; Human biomonitoring; Interlaboratory comparison investigation (ICI)